2023
DOI: 10.3390/jmse11061148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inclination Angles on the Hydrodynamics of Knotless Net Panels in Currents

Abstract: Knotless nets have been extensively used in sea cages and offshore fish farms; the explicit illustrations of local flow patterns and subjected hydrodynamic loads have practical implications for the safe operations of aquaculture pens in open oceans. However, the effects of inclination angles of knotless nets on local flow patterns have not yet been fully discussed. In this paper, the effects of inclination angles on local time-averaged and instantaneous flow fields, velocity reductions and force coefficients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(98 reference statements)
0
0
0
Order By: Relevance
“…Thierry et al [23] (2021) Used Numerical modeling based on fluid-structure interaction in two-way coupling to identify the turbulent flow that develops around different parts of the bottom trawl. Wang et al [24] (2023) numerically analyses the effects of inclination angles on local time-averaged and instantaneous flow fields, velocity reductions, and force coefficients and found that the inclination angles have dominant effects on the time-averaged velocity magnitudes around the net meshes and the hydrodynamic characteristic of netting.…”
Section: Introductionmentioning
confidence: 99%
“…Thierry et al [23] (2021) Used Numerical modeling based on fluid-structure interaction in two-way coupling to identify the turbulent flow that develops around different parts of the bottom trawl. Wang et al [24] (2023) numerically analyses the effects of inclination angles on local time-averaged and instantaneous flow fields, velocity reductions, and force coefficients and found that the inclination angles have dominant effects on the time-averaged velocity magnitudes around the net meshes and the hydrodynamic characteristic of netting.…”
Section: Introductionmentioning
confidence: 99%
“…Since a fishing net can change orientation with regard to the incoming flow, it is important to understand the effect of its angle of attack. For example, Simonsen et al [15], Zhao et al [16], Gansel et al [17], and Thierry et al [18], Tang et al [19], Mi et al [20], Yu et al [21], Endresen and Moe Føre [22], Wang et al [23] studied the effects of the flow speed and angle of attack on the drag and lift forces on nets through numerical simulation, empirical formulation, and/or physical model experiments. As a matter of fact, as the angle between the flow direction and the plane net is getting smaller, a shielding effect can drastically impact the drag coefficient.…”
Section: Introductionmentioning
confidence: 99%